EGF homologous sequences encoded in the genome of Drosophila melanogaster, and their relation to neurogenic genes. - Knust, E.; Dietrich, U.; Tepass, U.; Bremer, K.A.; Weigel, D.; Vassin, H.; Campos-Ortega, J.A. (The EMBO Journal, 1987)
The function of the neurogenic genes of Drosophila melanogaster is required for a normal pattern of commitment of neural and epidermal progenitor cells. In the course of searching for a molecular basis for the functional interrelationships that exist between the neurogenic genes, fragments of cloned DNA from the genes master mind (mam), Delta (Dl), Enhancer of split [E(spl)] and Notch (N) were hybridized to each other. Strong cross-hybridization was observed between a fragment of the Dl gene and a fragment of the N gene encoding a peptide with homology to several proteins of mammals, including the epidermal growth factor (EGF). Sequencing of this Dl fragment revealed an open reading frame encoding four EGF-like repeats with homology to the repeats found in the N gene. Screening genomic and cDNA libraries under conditions of reduced stringency with Dl and N probes that encode EGF-like repeats uncovered several cross-hybridizing clones, suggesting that other Drosophila genes may also encode such peptides. Part of a cross-hybridizing cDNA clone, derived from a gene located at position 95F on the third chromosome, was sequenced and found to encode five repeats with homology to those encoded by N and Dl. Preliminary evidence on the spatial pattern of transcription indicates that the gene at position 95F is regulated in its expression, as it is transcribed in all ectodermal derivatives, with the exception of the central nervous system. Indirect evidence suggests that this clone may derive from the crumbs (crb) gene, which is likely to be an hitherto unknown neurogenic gene.(ABSTRACT TRUNCATED AT 250 WORDS)